Rol' Kaliningradskoj oblasti v razvitii rossijsko-germanskih svjazej [The role of the Kaliningrad region in the development of Russian-German relations] - Fedorov Gennady; Gorodkov Mikhail; Zhukovsky Igor (Балтийский регион, 2011)
Germany is one of the principal partners of the Russian Federation. The Kaliningrad region plays a significant role in the development of partnership between the two countries, but the existing opportunities for development are not fully exploited. This article analyses the development, current state and prospects of an increasing role of the region in Russian-German cooperation. The authors emphasize the role of the Immanuel Kant Baltic Federal University as one of the leaders in the development of research and cultural links with German universities and research foundations. This publication is based on the authors' presentation at the round table discussion on the cooperation between Russian and German partner regions held on September 23, 2011 in the framework of the 8th International Conference on Transborder Cooperation: the Russian Federation, the European Union, and Norway (September 22—23, 2011, Kaliningrad). The article considers topical issues of Russian-German economic and cultural relations in the Kaliningrad region, which facilitate the development of Russian strategy for the integration of northwestern constituent entities into the economic and cultural space of the Baltic region.